160k views
2 votes

-4(3x+1)+x-3=15

2 Answers

8 votes


-4(3x+1)+x-3=15

start using the method PEMDAS

(parenthesis, exponents, multiplication, division, addition, subtraction)

so,

start with multiplying since its the third option to start with


-12x-4+x-3=15

now add like variables


-11x-7=15\\

continue by changing the signs to the other side +7 on both sides


-11x=22

now divide 11 on both sides


(22)/(-11) equals to negative 2

Answer :
-2

Hope this helps~

User Lia
by
4.6k points
9 votes


x = - 2is the answer

Step-by-step explanation -


-4(3x+1)+x-3=15


= > - 12x - 4 + x - 3 = 15


= > - 11x - 7 = 15


= > - 11x = 15 + 7


- 11x = 22
= > x = - (22)/(11)


= > x = - 2

~ Benjemin360

User Sid
by
5.1k points